The language of lamentation of women poets in pre-Islam and modern eras - Ismael, Shaymaa Omar (2017)
This study aims to explore the language used in lamentation by women poets in the pre-Islam and modern eras. For that purpose, three lamination samples by three outstanding women poets from the pre-Islam era and three from the modern era were selected. Accordingly, the study sample consisted of six lamentation poems. The study has four main objectives; to determine the poetic lexicon of the selected poets in expressing lamentation, to describe the expressive metaphorical narrative styles these poets relied on, to analyze their formation of the abstract and gestalt poetic imageries, and finally to compare between the three main issues mentioned in these objectives to determine the similarities and differences between the pre-Islam and modern lamentation poetry. To achieve these objectives, the analytical descriptive and the comparative approaches have been used to analyze and describe the poetic language of lamentation, and compare this language in the pre-Islam and modern eras. The findings of the study show that the language of lamentation (the poetic lexicon) has changed for modern women poets, and this change came as a result of the expansion in the language of each field of their poetic lexicon. This is true because the modern woman poet is more conscious compared with her pre-Islamic peers based on the influential language she has. Accordingly, she attempts to demonstrates her poetic skillfulness to recruit this lexicon in every filed of lamentation. As for the narrative styles, they varied in both eras. And women poets from both eras inscribed their language and lexicon with this variation to enhance the effectiveness of the expressions in the poem and link it directly to their feelings and emotions. Moreover, the abstract (audiovisual) image of women poets became an apex in their poems in the pre-Islamic and modern eras. However, pre-Islamic women poets notably focused on the visual image to show their experience, feelings, and ideas, whereas, modern women poets varied their poetry in terms of using the sensual image which was not confined to one or two types only. Regarding the gestalt image, it was completely different for each woman poet in both eras. Thus, the woman poet reflects her experience in the lamentation poem in sound steps and arranges her ideas and feelings of confusion and anxiety at the time of crisis.